Identifying hemophilia B carriers: Utility of aPTT, factor IX levels and ratios of factor IX to other Vitamin K dependent factors - Shu, Michael; Malcolmson, Caroline; Bosch, Alessandra; Markovic, Teodora; Wakefield, Cindy; Bouskill, Vanessa; Carcao, Manuel (Haemophilia : the official journal of the World Federation of Hemophilia, 2024)
Introduction Diagnosing hemophilia B (HB) carrier status is important to manage bleeding in carriers and to prevent bleeding in potential offspring. Without a family history of hemophilia, diagnosing HB carrier status is challenging. Genetic testing is the gold‐standard, however it is reserved for individuals with a high suspicion of carrier status. Aims To describe the distribution of activated partial thromboplastin time (aPTT) and factor IX coagulant (FIX:C) levels in HB carriers and assess the ratio of FIX:C to other Vitamin K dependent factors (FII:C, FVII:C, FX:C) as an indicator of HB carrier status. Methods In this retrospective, single‐centre cohort study, subjects were included if they were obligate or genetically proven HB carriers. Distributions of aPTT and FIX:C were described and the relationship between FIX:C levels in carriers and severity of familial HB was analysed. Ratios of FIX:C to FII:C, FVII:C, FX:C were calculated. Results Seventy‐two female HB carriers (median age: 34 years; IQR 24–43) were included. Median aPTT and FIX:C levels were 33.0 s [IQR 30.0–37.0] and 57 IU/dL [IQR 43–74]. Fifteen carriers (21%) had mild HB (FIX:C levels of 10–40 IU/dL). FIX:C levels trended higher in carriers of mild HB versus carriers of moderate/severe HB. In six carriers, the median ratio of FIX:C to other Vitamin K dependent factors was 0.44, with 92% of ratios being ≤ 0.75. Conclusion aPTT and FIX:C levels were unreliable in diagnosing HB carrier status. A low ratio of FIX:C to other Vitamin K dependent factors may be a useful marker of HB carrier status.